Reduced Mitochondrial Content, Elevated Reactive Oxygen Species, and Modulation by Denervation in Skeletal Muscle of Prefrail or Frail Elderly Women. (11th March 2019) - Sonjak, Vita; Jacob, Kathryn J; Spendiff, Sally; Vuda, Madhusudanarao; Perez, Anna; Miguez, Kayla; Minozzo, Fabio C; Spake, Carole; Morais, José A; Hepple, Russell T
Abstract: Denervation and mitochondrial impairment are implicated in age-related skeletal muscle atrophy and may play a role in physical frailty. We recently showed that denervation modulates muscle mitochondrial function in octogenarian men, but this has not been examined in elderly women. On this basis, we tested the hypothesis that denervation plays a modulating role in mitochondrial impairment in skeletal muscle from prefrail or frail elderly (FE) women. Mitochondrial respiratory capacity and reactive oxygen species emission were examined in permeabilized myofibers obtained from vastus lateralis muscle biopsies from FE and young inactive women. Muscle respiratory capacity was reduced in proportion to a reduction in a mitochondrial marker protein in FE, and mitochondrial reactive oxygen species emission was elevated in FE versus young inactive group. Consistent with a significant accumulation of neural cell adhesion molecule-positive muscle fibers in FE (indicative of denervation), a 50% reduction in reactive oxygen species production after pharmacologically inhibiting the denervation-mediated reactive oxygen species response in FE women suggests a significant modulation of mitochondrial function by denervation. In conclusion, our data support the hypothesis that denervation plays a modulating role in skeletal muscle mitochondrial function in FE women, suggesting therapeutic strategies in advanced age should focus on the causes and treatment of denervation.